Growing Up in New Zealand cohort alignment with all New Zealand births. (28th August 2014) - Morton, Susan M.B.; Ramke, Jacqueline; Kinloch, Jennifer; Grant, Cameron C.; Carr, Polly Atatoa; Leeson, Heidi; Lee, Arier Chi Lun; Robinson, Elizabeth
Abstract: Objective: To compare the birth characteristics of the Growing Up in New Zealand cohort with those of all New Zealand (NZ) births over a similar time period, and to describe cohort alignment to current NZ births. Method : The Growing Up in New Zealand longitudinal study recruited 6, 846 children from before birth via their pregnant mothers who were residing in the greater Auckland and Waikato regions during 2009 and 2010. Data were collected from mothers antenatally and six weeks after their expected delivery date, and from routine perinatal health records. These data were compared to Ministry of Health data for all births in NZ between 2007 and 2010. Results : The proportion of males and singleton births were not statistically different to national births. Compared to national births fewer of the cohort children were born low birth weight (4.9% vs. 6.1%, p <0.0001) or preterm (6.4% vs. 7.4%, p =0.001) and the cohort was expected to be more ethnically diverse than national births. Conclusion : Birth parameters for the cohort were generally closely aligned to all NZ births in 2007–2010. Some statistically significant differences reflected small absolute differences, attributable in some part to cohort recruitment requiring survival to six weeks post expected delivery. Implications : The explicit documentation of the alignment of the cohort to national data provides assurance that the study is well placed to deliver findings that can inform policy development relevant to the diversity of the contemporary NZ child population.